A miRNA-mediated attenuation of hepatocarcinogenesis in both hepatocytes and Kupffer cells - Yan Tian; Mingfeng Zhang; Mingjie Fan; Haixia Xu; Shunquan Wu; Sailan Zou; Yangmeng Wang; Dongmei Tang; Chunyan Zhang; Weidong Han; Hua Yu; Xianghui Fu; et al. (Molecular Therapy: Nucleic Acids, 2022)
MicroRNAs (miRNAs) are small noncoding RNAs that regulate a variety of physiological and pathological functions. miR-26a is one of the many miRNAs that have been identified as regulators of cancer development and as potential anticancer drug targets. However, the specific cellular and molecular mechanisms by which miR-26a attenuates hepatocarcinogenesis are still elusive. Here, we interrogated mouse models with miR-26a cell-specific overexpression in either hepatocytes or myeloid cells to show that miR-26a strongly attenuated the chemical-induced hepatocellular carcinoma (HCC). miR-26a overexpression broadly inhibited the inflammatory response in both hepatocytes and macrophages by decreasing several key oncogenic signaling pathways in HCC promotion. These findings thus reveal new insights into a concerted role of miR-26a in both hepatocytes and Kupffer cells to suppress hepatocarcinogenesis, thereby highlighting the potential use of miR-26a mimetics as potential approaches for the prevention and treatment of HCC.